PROMOTING RESILIENCE AND WELL-BEING FOR INDIVIDUALS, FAMILIES, AND COMMUNITIES IN PSYCHOSOCIAL CRISIS - Goldner Vukov, Mila; Mijalković, Snežana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: It is estimated that up to 70% of people experience at least one serious traumatic event during their lives. Trauma usually causes a psychosocial crisis, which is a state of instability and danger. Trauma and the psychosocial crisis are addressed at the level of the individual, the family, and the community. Promoting resilience and well-being is very useful in helping a person “bounce back” after encountering adversity.Objective: This paper explores the dynamics of psychosocial crisis and the ways of promoting resilience and well-being at the individual, family, and community levels.Materials and methods: A literature review was conducted on psychosocial crises, their causes and consequences, as well as on resilience and well-being as key resources for addressing these challenges.Results: Resilience factors – such as optimism, facing one’s fear, a strong moral compass, religion and spirituality, social support, cognitive and emotional flexibility, and a sense of meaning and purpose – play a crucial role in coping with psychosocial crises. Well-being can be further enhanced by prioritizing physical health, nurturing social connections, and engaging in mental stimulation.Conclusion: Psychosocial crises can be observed on several levels – maturational, situational, existential, spiritual, and adventitious. If trauma is not properly addressed and the crisis persists, it may lead to both intergenerational and transgenerational trauma. Strengthening resilience and enhancing well-being at the levels of the individual, family, and society are essential strategies for coping with trauma and mitigating negative outcomes such as PTSD, substance abuse, suicidality, depression, and physical health problems. By fostering resilience and well-being, traumatic experiences and psychosocial crises can be transformed into opportunities for personal, family, and social growth and development.
Keywords: trauma; psychosocial crisis; resilience; well-being